Design strategies for solar photovoltaic integration in rural areas - Saadon, Intan Mastura; Ahmad, Emy Zairah; Norddin, Nurbahirah; Idris, Norain (Institute of Advanced Engineering and Science, 2025)
This study explores the optimization of photovoltaic (PV) systems in the Sungai Tiang Camp region, Malaysia, with a focus on determining the ideal tilt angles to maximize energy generation in a tropical environment while incorporating a cost analysis. While existing studies optimize tilt angles for energy maximization in temperate regions, this study addresses the unique climatic and socio-economic conditions of rural Malaysia. Unlike fixed-tilt assumptions common in prior work, this research explores cost-effective, manually adjustable systems tailored for local weather patterns and rural affordability. To address this, the study examines the relationship between tilt angle, solar irradiance, temperature and output power. The results are analyzed to identify optimal configurations. Results reveal that tilt angles between 5° and 10° deliver the highest energy output, with slight seasonal adjustments for efficiency improvement. These findings align with Malaysia's tropical solar profile, offering practical insights for micro-scale solar deployments in similar climates. By addressing the unique needs of remote areas, this research contributes to bridging the gap in localized PV studies. Its outcomes not only enhance the understanding of solar PV performance in tropical conditions but also provide valuable guidelines for rural electrification and sustainable energy solutions in equatorial regions worldwide.